1992
DOI: 10.1116/1.578049
|View full text |Cite
|
Sign up to set email alerts
|

Atom assisted sputtering yield amplification

Abstract: At first sight one might assume that it is unlikely to influence the sputtering yield of a specific ion/substrate combination by any external means. However, we have found that such an influence may well be introduced. The sputtering yield is predominantly determined by the ion/substrate momentum transfer efficiency and the energy of the incoming ion. Sputter erosion of, e.g., carbon atoms by argon ions from a carbon substrate exhibits a very low sputtering yield. Due to the difference in masses between carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 0 publications
1
17
0
1
Order By: Relevance
“…W) to the target material [8]. This effect originates in a reduction of the implantation depth of the light element due to an increased stopping power and is known as "sputter yield amplification" (SYA) [9]. Choosing conditions that allow depositing light particles energetically on a layer of a much heavier material, such a SYA-effect should also be observable at the interfaces of laser deposited multilayers.…”
Section: Introductionmentioning
confidence: 99%
“…W) to the target material [8]. This effect originates in a reduction of the implantation depth of the light element due to an increased stopping power and is known as "sputter yield amplification" (SYA) [9]. Choosing conditions that allow depositing light particles energetically on a layer of a much heavier material, such a SYA-effect should also be observable at the interfaces of laser deposited multilayers.…”
Section: Introductionmentioning
confidence: 99%
“…In 1992, Berg et al (16) reported an effect they called 'atom-assisted sputtering yield amplification.' If light materials such as carbon are bombarded by argon ions, sputtering is not very effective, since the momentum transfer is low and the collision cascade may spread deep into the bulk of the target.…”
Section: Sputter Yield Amplification and Serial Cosputteringmentioning
confidence: 99%
“…It combines the possibility to prepare coatings with adjustable doping concentration; furthermore it allows increasing the effective deposition rate via the socalled sputtering yield amplification effect (SYA) [3]. The technology has the following advantages over conventional sputtering:…”
Section: Introductionmentioning
confidence: 99%